A Review of IPO Under-pricing Phenomenon in Asia - Albada, Ali; Yong, Othman (UUM Press, 2019)
This paper reviews the current status of IPO research in Asia, especially when it comes to the issue of the under-pricing phenomenon. This interest stems from the increasing attention that some of the Asia Pacific region countries have, due to their higher average initial returns in comparison to other developed and developing countries. In this review, we identify the determinants for the high levels of under-pricing as reported in the literature. We find that the regulatory environment of these Asian countries is the most reasonable source for such under-pricing, as it sets it apart from other developed and developing countries.